2008
DOI: 10.1007/s00296-008-0741-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of Behcet’s disease in Egypt

Abstract: Behcet's disease (BD) is a chronic relapsing multisystem disease of unknown etiology. Ethnic origin is one of the factors that may modulate the prevalence and the expression of BD. To study the clinical characteristics of Egyptian patients with BD, and compare the pattern of the disease in Egyptians with studies from other countries. Sixty-three patients with BD were studied over a 4-year period. A rheumatologist, dermatologist, neurologist and other specialists as indicated assessed the patients clinically. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
6
33
0
1
Order By: Relevance
“…In a recent study by Vaiopoulos et al [8], OU (64.36 %), EN (7.42 %) and GU (6.93 %), and in a previous study by Zouboulis et al [3], OU (60.9 %), ocular (11.0 %) and articular (9.7 %) involvements were found to be the most common onset manifestations in a Greek population. El Menyawi et al [9] from Egypt reported OU to be the most frequent onset manifestation (63.4 %), followed by GU (26.9 %) and deep venous thrombosis (7.9 %). In the recent study by Pipitone et al [10], OU (78.3 %), GU (29.2 %) and eye involvement (20 %), and in a previous study by Salvarani et al [11], OU (77.8 %), GU (16.7 %) and EN (22.2 %) were reported to be the most common onset presentations in an Italian population.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study by Vaiopoulos et al [8], OU (64.36 %), EN (7.42 %) and GU (6.93 %), and in a previous study by Zouboulis et al [3], OU (60.9 %), ocular (11.0 %) and articular (9.7 %) involvements were found to be the most common onset manifestations in a Greek population. El Menyawi et al [9] from Egypt reported OU to be the most frequent onset manifestation (63.4 %), followed by GU (26.9 %) and deep venous thrombosis (7.9 %). In the recent study by Pipitone et al [10], OU (78.3 %), GU (29.2 %) and eye involvement (20 %), and in a previous study by Salvarani et al [11], OU (77.8 %), GU (16.7 %) and EN (22.2 %) were reported to be the most common onset presentations in an Italian population.…”
Section: Discussionmentioning
confidence: 96%
“…Superficial thrombophlebitis was observed in 2% of patients in Turkey, 19% in China, and 15% in Egypt . Arterial lesions were found in 0.3% of patients in Turkey, 11% in Egypt, and 10% in Tunisia…”
Section: Discussionmentioning
confidence: 99%
“…Deep vein thrombosis is the main feature, which was seen in 3% of patients in Turkey, 33% in Tunisia, and 41% in Egypt . Superficial thrombophlebitis was observed in 2% of patients in Turkey, 19% in China, and 15% in Egypt . Arterial lesions were found in 0.3% of patients in Turkey, 11% in Egypt, and 10% in Tunisia…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was higher than the rate of 39.7% found in Egypt. [10][11][12][13][14] Tugal-Tutkun et al [11] showed in their large observational case series that the rate of genital ulcers was 59.8%. This is lower than the rate found in our present study (82.8%), which might reflect the heterogenity of the population living in the Çukurova region since this part of Turkey has distinct ethnic properties compared with other regions.…”
Section: Discussionmentioning
confidence: 99%